Effect of storage duration on the stored pupae of parasitoid Bracon hebetor (Say) and its impact on parasitoid quality (Bangladesh Journal of Agricultural Research, 2016)
The ecto-endo larval parasitoid, Bracon hebetor (Say) is an important biocontrol agent. Effective storage methods for B. hebetor are essential for raising its success as a commercial bio-control agent against lepidopteran pests. The study was undertaken to determine the effect of storage duration on the pupae of Bracon hebetor in terms of pupal survival, adult emergence, percent parasitism, female and male longevity, female fecundity and sex ratio. Three to four days old pupae were stored for 0, 1, 2, 3, 4, 5, 6, 7 and 8 weeks at 4 ± 1oC. The ranges of time for adult emergence from stored pupae, production of total adult, survivability of pupae, parasitism of host larvae by the parasitoid, longevity of adult female and male and fecundity were 63.0 -7.5 days, 6.8-43.8/50 host larvae, 13.0-99.5%, 0.0 -97.5%, 0.00-20.75 days, 0.00-17.25 days and 0.00- 73.00/50 female, respectively. The time of adult emergence and mortality of pupae increased but total number of adult emergence, survivability of pupae, longevity of adult female and male decreased gradually with the progress of storage period of B. hebetor pupae. The prevalence of male was always higher than that of female. Therefore, short-term storage of B. hebetor pupae could be stored for up to 4 weeks without disturbing the functioning of the parasitoid. It is important for sustaining and accumulating large numbers of parasitoids in mass rearing programs and subsequent use of field application.Bangladesh J. Agril. Res. 41(2): 297-310, June 2016